Evaluation and performance of a newly developed patient-reported outcome instrument for diarrhea-predominant irritable bowel syndrome in a clinical study population. (September 2017) - Delgado-Herrera, Leticia; Lasch, Kathryn; Zeiher, Bernhardt; Lembo, Anthony J.; Drossman, Douglas A.; Banderas, Benjamin; Rosa, Kathleen; Lademacher, Christopher; Arbuckle, Rob
Background: To evaluate the psychometric properties of the newly developed seven-item Irritable Bowel Syndrome – Diarrhea predominant (IBS-D) Daily Symptom Diary and four-item Event Log using phase II clinical trial safety and efficacy data in patients with IBS-D. This instrument measures diarrhea (stool frequency and stool consistency), abdominal pain related to IBS-D (stomach pain, abdominal pain, abdominal cramps), immediate need to have a bowel movement (immediate need and accident occurrence), bloating, pressure, gas, and incomplete evacuation. Methods: Psychometric properties and responsiveness of the instrument were evaluated in a clinical trial population [ClinicalTrials.gov identifier: NCT01494233]. Results: A total of 434 patients were included in the analyses. Significant differences were found among severity groups ( p < 0.01) defined by IBS Patient Global Impression of Severity (PGI-S) and IBS Patient Global Impression of Change (PGI-C). Severity scores for each Diary and Event Log item score and five-item, four-item, and three-item summary scores were calculated. Between-group differences in changes over time were significant for all summary scores in groups stratified by changes in PGI-S ( p < 0.05), two of six Diary items, and three of four Event Log items; a one-grade change in PGI-S was considered a meaningful difference with mean change scores on all Diary items −0.13 to −0.86 [standard deviation (SD) 0.79–1.39]. Similarly, for patients who reported being 'slightly improved' (considered a clinically meaningful difference) on the PGI-C, mean change scores on Diary items ranged from −0.45 to −1.55 (SD 0.69–1.39). All estimates of clinically important change for each item and all summary scores were small and should be considered preliminary. These results are aligned with the previous standalone psychometric study regarding reliability and validity tests. Conclusions: These analyses provide evidence of the psychometric properties of the IBS-D Daily Symptom Diary and Event Log in a clinical trial population.